A Comparative Study on the Correlations between (i) Mathematics Quotient (MQ) and Nonverbal Intelligence Quotient (NVIQ) & (ii) Mathematics Quotient (MQ) and Draw-a-Person Intelligence Quotient (dIQ) in Primary 3 Children with Selective Mutism - Chia, Noel Kok Hwee; Tee Ng, Angie Gek; Kheng Tan, Stacey Siew; Wee, Lay Hwee (Journal of the American Academy of Special Education Professionals, 2011)
Although selective mutism does not necessarily interfere with academic performance, little is known about the impact of persistent selective mutism on the academic development as children grow older. It can become very difficult for psychologists, therapists and educators to assess the knowledge and learning of children with selective mutism as they do not speak or communicate easily. Hence, it is often difficult to administer the verbal scale of a standard psychological assessment such as Wechsler Intelligence Scale for Children-Fourth Edition (WISC-IV) or Slosson Full-Range Intelligence Test (SFRIT). In this study, 15 children with selective mutism undergoing treatment at the Learning Disabilities Center for their condition as well as poor performance in mathematics learning were assessed on two intelligence tests that do not require spoken language: the Draw-a-Person: Test of Intelligence (DAP:IQ) to obtain the Draw-a-Person IQ (dIQ) or the Test of Nonverbal Intelligence Test-Third Edition (TONI-3) to obtain the Nonverbal IQ (NVIQ). Their performance in mathematics learning was assessed using the Test of Mathematical Abilities-Second Edition (TOMA-2) to obtain their respective Mathematics Quotients (MQs). An investigation was done to find out the correlations between their (i) dIQ and MQ for one group (n=8), and (ii) NVIQ and MQ for another group (n=7).